Overgrowth Syndromes—Evaluation, Diagnosis, and Management - Manor, Joshua; Lalani, Seema R. (Frontiers in Pediatrics, 2020)
Abnormally excessive growth results from perturbation of a complex interplay of genetic, epigenetic, and hormonal factors that orchestrate human growth. Overgrowth syndromes generally present with inherent health concerns and in some instances, an increased risk of tumor predisposition that necessitate prompt diagnosis and appropriate referral. In this review, we introduce some of the common overgrowth syndromes, along with their molecular mechanisms, diagnostics, and medical complications for improved recognition and management of patients affected with these disorders.